Social arithmetics: learning from Indramayu traditional market traders in doing calculations - Sudirman, Sudirman; Rodríguez-Nieto, Camilo Andrés; Bonyah, Ebenezer; Takiveikata, Sereima; Dejarlo, Jenisus O. (Nashir Al-Kutub Indonesia, 2023)
This study aims to reveal the counting patterns performed by Indramayu Traditional Market Traders in buying and selling activities. This research uses a qualitative approach with a descriptive case study design. The sampling technique used was purposive sampling by collecting data using snowball sampling. The participants involved in this study were three traders. Data analysis in this study used qualitative analysis from Milles & Huberman, which consisted of 4 stages: data collection, data reduction, data presentation, and conclusion. The results of this study indicate that Indramayu traditional market traders have used mathematical concepts such as addition, subtraction, multiplication, and division operations in buying and selling activities. Besides that, this study also found that traditional traders use backward calculations (from front to back) in buying and selling their wares. The calculation method traditional trader’s use differs from that usually taught in schools. This method has become a standard pattern to make it easier for them to count. Based on these findings it implies that there are other ways of operating information activities that can be used by schools formally. In addition, teachers must be able to provide the context in everyday life, especially in buying and selling activities in traditional markets, to students so that students get a broader understanding of solving problems in arithmetic material.